2020
DOI: 10.1210/clinem/dgaa613
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Long-term Follow-up of Patients with Diabetes Due To PTF1A Enhancer Mutations

Abstract: Context Biallelic mutations in the PTF1A enhancer are the commonest cause of isolated pancreatic agenesis. These patients do not have severe neurological features associated with loss-of-function PTF1A mutations. Their clinical phenotype and disease progression have not been well characterised Objective To evaluate phenotype and genotype characteristics and long-term follow-up of patients with PTF1A enhancer mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
3
10
0
1
Order By: Relevance
“…Also, previous functional analyses showed that a homozygous mutation could distrust enhancer activity and is likely to decrease in PTF1A expression during pancreatic development. This result confirms a diagnosis of neonatal diabetes and exocrine pancreatic insufficiency due to a recessive PTF1A mutation (11,12). Therefore, we evaluated sequencing the coding regions of ABCC8, KCNJ11, INS, and EIF2AK3 genes and also the PTF1A gene in our study.…”
Section: Review Of Previously Reported Casessupporting
confidence: 75%
“…Also, previous functional analyses showed that a homozygous mutation could distrust enhancer activity and is likely to decrease in PTF1A expression during pancreatic development. This result confirms a diagnosis of neonatal diabetes and exocrine pancreatic insufficiency due to a recessive PTF1A mutation (11,12). Therefore, we evaluated sequencing the coding regions of ABCC8, KCNJ11, INS, and EIF2AK3 genes and also the PTF1A gene in our study.…”
Section: Review Of Previously Reported Casessupporting
confidence: 75%
“…None of the patients had severe neurological features; however, additional features such as growth retardation, anaemia and cholestasis were common. 25 Isolated pancreatic agenesis has also been reported in two families who were homozygous for the PTF1A missense mutation, p.(Pro191Thr). In vitro studies suggested that this mutation is likely to result in partial loss of function, thus potentially explaining the absence of the severe neurological features caused by coding loss of function mutations.…”
Section: Neonatal Diabetes Caused By Autosomal Recessive Ptf1a Mutationsmentioning
confidence: 98%
“…Homozygous missense (hypomorphic) mutations in the same gene cause neonatal diabetes mellitus, associated with pancreatic aplasia/hypoplasia but without neurological manifestations (Houghton et al, 2016). In addition, biallelic mutations in PTF1A enhancer regions have been associated with pancreas agenesis without extra pancreatic or neurological manifestations (Weedon et al, 2014, Demirbilek et al, 2020. Indeed, an initial study showed that recessive mutations in a 400 bp distal PTF1A enhancer located 25 kb downstream PTF1A were causal of isolated pancreas agenesis in ten independent families (Weedon et al, 2014).…”
Section: Genetic Alteration and Clinical Phenotypementioning
confidence: 99%
“…A recent genetic and phenotypic follow-up study performed in a very large cohort of patients with PTF1A enhancer mutations (30 cases) identified one additional recessive mutation associated with isolated pancreatic agenesis, and provided a very detailed analysis of the clinical characteristics of the patients identifying recurrent extrapancreatic features that accompany the pancreatic manifestations e.g. hyperferritinemia, anemia, transient mild to severe elevation in liver trans-aminases between others (Demirbilek et al, 2020).…”
Section: Genetic Alteration and Clinical Phenotypementioning
confidence: 99%